PELATIHAN MANAJEMEN KURIKULUM PENDIDIKAN AGAMA ISLAM TINGKAT MADRASAH IBTIDAI’AH - Siti Aisyah ('Ibadatuna : Jurnal Pengabdian Masyarakat, 2022)
Abstract The article describes the Islamic religious education curriculum management training at the madrasah ibtidai'ah level in Banyuputih Kidul Lumajang. Research using constructive methods. Based on the results of the research, the Islamic religious education curriculum management training at Madrasah Ibtidai'ah in Banyuputih Kidul Lumajang was carried out in stages: 1) determining the model in development and analyzing needs and situations, 2) determining objectives and formulating contents in the curriculum, 3) selecting methods in developing the curriculum, 4) implementing the curriculum and evaluating the curriculum on an ongoing basis. Curriculum development management assistance is a general procedure in designing, implementing, and evaluating a curriculum